City-based learning – koncepcja uczenia się poprzez miasto. Tło teoretyczne, podstawowe założenia, przyszłe konteksty rozwoju i implementacji - Kruszwicka, Agnieszka; Klichowski, Michał (Studia Edukacyjne, 2018)
Currently, over a half of the world’s population lives in cities. It is estimated that by 2050 at least 85 per cent of Europeans will have lived in European cities. This trend is related to the fact that today cities are spaces of permanent learning in authentic contexts, which is fostered by the development of new technologies. However, little is known about the city-based learning concept, which is crucial for this type of technology-enhanced learning. Here, we discuss the theoretical background, basic assumptions and future contexts of development and implementation of this idea. Firstly, we demonstrate that city-based learning is contingent on such theories as urban studies, pedagogy of place, as well as urban education, explorative learning, learning outside the classroom, mobility of learning space or on-street activity. Secondly, we show that smartphones, tablets, GPS, educational cloud, and digital textbooks are technologies for city-based learning. We conclude that cities connected to an educational cloud (which is full of educational resources and serves as a platform for educational communication) are unique environments for students equipped with mobile tools. Finally, we point out a new project on a city-based learning implementation.